Mathematical Representation Ability-Based Mathematical Contextual Problems of Sequences and Progression Material - Sri Wahyuning, Lis Diana; Nida Sri Utami (Vygotsky: Jurnal Pendidikan Matematika dan Matematika, 2024)
This research objective is to analyze and explain the student’s capacity for mathematical representation based on mathematical contextual problems of arithmetic and geometric sequences and progression material. Students enrolled in SMA 1 Sukoharjo X.E10 were the subject of this research. The data collection process used interviews, tests, and documentation. This research used a descriptive research approach with a qualitative research type. Based on the findings of this research, students who have visual representation skills in mathematics are more likely to complete challenges that involve visuals, such as diagrams. Typically, mathematically symbolic representation-capable pupils utilize mathematical formulas and symbols to solve problems. Furthermore, students who have the ability to verbally represent mathematics have a tendency to encrypt problem-solving steps into words.